Quantification of Electromechanical Coupling to Prevent Inappropriate Implantable Cardioverter-Defibrillator Shocks - Keene,D; Shun-Shin,M; Arnold,A; Howard,J; Lefroy,D; Davies,W; Lim,PB; Ng,FS; Koa-Wing,M; Qureshi,N; Linton,N; Shah,J; et al. (JACC: Clinical Electrophysiology, 2019)
Objective To test specialised processing of laser Doppler signals for discriminating ventricular fibrillation(VF) from common causes of inappropriate therapies.BackgroundInappropriate ICD therapies remain a clinically important problem associated with morbidity and mortality.Tissue perfusion biomarkers, to assist automated diagnosis of VF, suffer the vulnerability of sometimes mistaking artefact and random noise for perfusion, which could lead to shocks being inappropriately withheld. MethodsWe developed a novel processing algorithm that combines electrogram data and laser Doppler perfusion monitoring, as a method for assessing circulatory status. We recruited 50 patients undergoing VF induction during ICD implantation. We recorded non-invasive laser Doppler and continuous electrograms, during both sinus-rhythm and VF. For each patient we simulated two additional scenarios that may lead to inappropriate shocks: ventricular-lead fracture and T-wave oversensing. We analysed the laser Doppler using three methods for reducing noise: (i)Running Mean, (ii)Oscillatory Height, (iii)a novel quantification of Electro-Mechanical coupling which gates laser Doppler against electrograms. We additionally tested the algorithm during exercise induced sinus tachycardia.ResultsOnly the Electro-mechanical coupling algorithm found a clear perfusion cut-off between sinus rhythm and VF (sensitivity and specificity 100%). Sensitivity and specificity remained 100% during simulated lead fracture and electrogram oversensing. (AUC: Running Mean 0.91, Oscillatory Height 0.86, Electro-Mechanical Coupling 1.00). Sinus tachycardia did not cause false positives.ConclusionsQuantifying the coupling between electrical and perfusion signals increases reliability of discrimination between VF and artefacts that ICDs may interpret as VF. Incorporating such methods into future ICDs may safely permit reductions of inappropriate shocks.